ASP.NET 2.0 unleashed - Walther, Stephen (Sams, 2006)
ASP.NET 2.0 Unleashed covers virtually all features of ASP.NET 2.0 including more than 50 new controls, Personalization, Master Pages and Web Parts. All code samples will be presented in VB and C♯. Throughout the more than 2,000 pages readers are shown how to develop state-of-the-art Web applications using Microsoft's latest development tools. This is a resource designed to be referenced over and over.